Kualitas Daging Kambing Terfermentasi (Bekamal) dengan Waktu Pemeraman yang Berbeda - Muhammad Habbib Khirzin; Sefri Ton; Alfitrah Sari (CV. Ulil Albab Corp, 2023)
Bekamal is a typical fermented meat from Banyuwangi Regency. Bekamal is made from minced meat with salt and brown sugar added and then stored for a certain time using a clay storage (kendil). Bekamal products are starting to be difficult to find in the market. Reinforcement of processed products based on local wisdom needs to be done so that the products are not lost. One way of strengthening can be done by assessing the quality of nutrition and consumer acceptance. The purpose of this study was to determine the physicochemical and organoleptic characteristics of bekamal goats with different fermentation times. This study used a nonfactorial completely randomized design (CRD) with fermentation time variables (1, 2, 3, and 4 weeks). The research data were analyzed using analysis of variance (ANOVA) and if there were significant differences, the duncan multiple range test (DMRT) was continued. The results showed that different fermentation times had a significant effect (P<0.05) on pH value, total acid, water content, water holding capacity, color, aroma, texture and taste. Bekamal which was fermented for 4 weeks gave the best results from all parameters. This product can be developed into fermented meat-based processed products.